2011
DOI: 10.1016/j.tetlet.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Use of co-grinding as a solvent-free solid state method to synthesize dibenzophenazines

Abstract: Many synthetic methods exist for dibenzoquinoxalines but only a few for dibenzophenazines and their aza derivatives and even less are 'green'. Some dibenzophenazines and dibenzopyridoquinoxaline have been efficiently obtained with good to excellent yield by a very simple method which does not require use of solvent or catalyst. Solid phase synthesis using co-grinding presents thus many advantages in developing greener synthetic organic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…To explore the reason of this stability, FT-IR spectrum of 4-chlorophenyl diazonium salt was studied ( Figure 3). In this spectrum, the ethanolic OH and existing moisture in nano silica gel and BF 3 According to this information, the structure of diazonium salts supported on nano BF 3 ·SiO 2 was Figure 2. XRD patterns of (a) nano silica gel and (b) nano BF 3 ·SiO 2 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…To explore the reason of this stability, FT-IR spectrum of 4-chlorophenyl diazonium salt was studied ( Figure 3). In this spectrum, the ethanolic OH and existing moisture in nano silica gel and BF 3 According to this information, the structure of diazonium salts supported on nano BF 3 ·SiO 2 was Figure 2. XRD patterns of (a) nano silica gel and (b) nano BF 3 ·SiO 2 .…”
Section: Resultsmentioning
confidence: 82%
“…At the beginning of the new century, synthesis of organic compounds using grinding technique under solvent-free conditions (1)(2)(3)(4)(5)(6)(7)(8) has received much attention, as it provides manipulative simplicity, greater selectivity, easier workup, lesser reaction times, and higher yields which match with the green chemistry protocol. On the other side, more attention has been directed toward the application of solid acids in organic synthesis because such reagents not only simplify purification processes but also help prevent release of reaction residues into the environment (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Carlier et al [38] showed that reaction between diamines and 1,2-or 1,3-dicarbonyls by ball milling provided dibenzophenazines and dibenzopyridoquinoxaline derivatives (Scheme 28) without any catalyst or solvent. These products were also obtained in high yields.…”
Section: Ball-milling In Heterocycles Synthesismentioning
confidence: 99%
“…The mechanisms of mechanochemical transformations are often complex and different from usual thermal or photochemical mechanisms [2,3]. The method of ball milling is a widely used process in which mechanical force is used to achieve chemical processing and transformations [4].…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%